Sustainable Waste Management In Bima City: Social, Institutional, And Technological Perspectives - Endang Sri Sumanti (Jurnal Sistem Informasi Bisnis, 2025)
Population growth and economic activity in Bima City have significantly increased the volume of waste generated, reaching 80.6 tons per day. However, the management capacity, which only covers 53.16% of the area, has led to a decline in environmental quality, such as water, air, and soil pollution. This study aims to analyze the impact of waste management on environmental conditions in Bima City, considering social, institutional, and technological factors of waste management. The research method used an explanatory quantitative-descriptive approach with Structural Equation Modeling (SEM) analysis of 200 respondents consisting of the community, sanitation workers, and environmental managers. The variables examined include policy and institutions (ORG), community participation (PART), technology and infrastructure (TECH), and environmental conditions (ENV). The results showed that policy and institutions had a positive effect on the effectiveness of waste management (β = 0.34; p < 0.001), while community participation had a significant effect on environmentally friendly behavior (β = 0.42; p < 0.001), while technological infrastructure has an indirect effect on environmental conditions through management effectiveness (β = 0.28; p < 0.01). Overall, good waste management contributes to a 57.8% improvement in environmental quality. This study emphasizes the importance of synergy between policy support, social participation, and the application of sustainable technology to achieve effective environmental management in Bima City.